Controle jurídico dos incentivos fiscais - Pinho, Mariana Corrêa de Andrade (2017)
This paper focuses on the legal control instruments of tax incentives, based on a functional analysis of Tax Law. To achieve that, it proposes a return to the origins of Tax Law, that is born within the Science of Finance and whose main role is to regulate the mean to provide public requirements. Based on this premise, it critically addresses the current legal framework of tax incentives and the implications of applying the principle of equality in the extrafiscality. Therefore, the intermediate chapters are devoted to the principle of equality, to the notion of extrafiscality and to the concept of tax incentives. At last, discusses the need to combine the legislative discretion regarding tax benefits with the legal control instruments, especially those resulting from the application of the principle of proportionality